Contraceptive Acceptance among Eligible Couples Residing in Rajshahi City Corporation - Sultana, S; Jahan, M Sarwar; Islam, M Mofakharul (TAJ: Journal of Teachers Association, 2009)
A descriptive type of cross sectional study was carried out among the eligible couples residing in Rajshahi City Corporation during the period of three moths from 1st April to 30th June, 2005 with a view to collect information about the acceptance of contraceptive methods from 366 respondents with 50 male and 316 female. The mean age in female respondents is 27.22 yrs. and male 30.2 years. The mean number of living children is 2.6 in female respondents and 2.1 in male respondents. Majority of the respondents 65.51% were housewives. 11.71% of the respondents were illiterate. Most of the respondents had knowledge regarding contraceptive methods. In this study 93.67% of female respondents & 20% of male respondents were currently using contraceptive methods. The modern methods were oral pill 21.6% IUCDs 14.9%, injection 35.14%, Norplant 12.16%, condom 16.0%, safe period 6.76%, Tubectomy 9.46%, Vasectomy 4.0% and 6.13% were non acceptors of contraceptives. Temporary methods were more accepted than the permanent methods. 84.2% female and 16% male respondents accepted temporary methods. Permanent methods were adopted by 9.5% female and by 4% male only. Study shows that percentage of the contraceptive method users increased with the level of education. The major causes for not accepting contraceptive methods were fear of complications (46.7% among female and 23% among male), opposition of the elderly (13% among female and 6.4% among male) and 55% male said about female partner's preference as user, so they did not use methods by them. Major causes for not accepting permanent methods were fear of operation (43% among female and 55.6% among male), religious barrier (31.9% among female and 42.2% among male), fear for decreased physical ability (12.5% among female and 2.2% among male) and lastly familial pressure (among 12.5% female). Most of the female 50.9% and only 2% male respondents faced problems during contraceptive use and the nature of the problem were mainly physical complication, spouse opposition and 3.16% female faced unwanted pregnancy while practicing method. Hospital supplies of contraceptives to the respondents were more i.e. 23% and 24% by the NGOs worker. It encourages people to accept contraceptive methods. Main causes of dropout among the respondents were desire for more children specially son preference and also due to health problems. doi: 10.3329/taj.v20i1.3083 TAJ 2007; 20(1): 11-16